Trust Management in the Internet of Vehicles: A Survey of the State-of-the-Art - Yingxun, Wang; Adnan, Mahmood; Mohamad Faizrizwan, Mohd Sabri; Hushairi, Zen (IEEE, 2026)
The Internet of Vehicles (IoV) represents a transformative paradigm within the context of Intelligent Transportation System (ITS) with the aim to enhance road safety, traffic efficacy, environmental sustainability, and user convenience. However, as IoV networks increase in scale and complexity, ensuring trustworthy interactions among vehicles, infrastructure, and service providers becomes paramount. This paper, therefore, presents a comprehensive review of trustworthiness management for an IoV network. Firstly, the transition of Vehicular Ad hoc Networks (VANETs) to IoV followed by an examination of the notion of trust in various domains has been explored. Subsequently, the characteristics of trust, salient constituents of trust, key trust attributes, trust evaluation parameters, and trust-based attacks in the context of an IoV network have been delineated. Moreover, the five key processes involved in the trust management, i.e., trust formation, trust propagation, trust aggregation, trust update, and trust decision, have been investigated vis-à-vis the state-of-the-art. Furthermore, the advanced trust management models, i.e., conventional and artificial intelligence-based ones, have been analyzed in-depth. Finally, simulation tools and datasets employed in IoV-based trust management models have been introduced, along with an outline of key open research directions in this domain.